A candidate glycoconjugate vaccine induces protective antibodies in the serum and intestinal secretions, antibody recall response and memory T cells and protects against both typhoidal and non-typhoidal Salmonella serovars - Haldar, Risha; Dhar, Amlanjyoti; Ganguli, Debayan; Chakraborty, Suparna; Pal, Ananda; Banik, George; Miyoshi, Shin-ichi; Das, Santasabuj (Frontiers in Immunology, 2024)
Human Salmonella infections pose significant public health challenges globally, primarily due to low diagnostic yield of systemic infections, emerging and expanding antibiotic resistance of both the typhoidal and non-typhoidal Salmonella strains and the development of asymptomatic carrier state that functions as a reservoir of infection in the community. The limited long-term efficacy of the currently licensed typhoid vaccines, especially in smaller children and nonavailability of vaccines against other Salmonella serovars necessitate active research towards developing a multivalent vaccine with wider coverage of protection against pathogenic Salmonella serovars. We had earlier reported immunogenicity and protective efficacy of a subunit vaccine containing a recombinant outer membrane protein (T2544) of Salmonella Typhi in a mouse model. This was achieved through the robust induction of serum IgG, mucosal secretory IgA and Salmonella-specific cytotoxic T cells as well as memory B and T cell response. Here, we report the development of a glycoconjugate vaccine, containing high molecular weight complexes of Salmonella Typhimurium O-specific polysaccharide (OSP) and recombinant T2544 that conferred simultaneous protection against S. Typhi, S.ParatyphiParatyphi, S. Typhimurium and cross-protection against S. enteritidis in mice. Our findings corroborate with the published studies that suggested the potential of Salmonella OSP as a vaccine antigen. The role of serum antibodies in vaccine-mediated protection is suggested by rapid seroconversion with high titers of serum IgG and IgA, persistently elevated titers after primary immunization along with a strong antibody recall response with higher avidity serum IgG against both OSP and T2544 and significantly raised SBA titers of both primary and secondary antibodies against different Salmonella serovars. Elevated intestinal secretory IgA and bacterial motility inhibition by the secretory antibodies supported their role as well in vaccine-induced protection. Finally, robust induction of T effector memory response indicates long term efficacy of the candidate vaccine. The above findings coupled with protection of vaccinated animals against multiple clinical isolates confirm the suitability of OSP-rT2544 as a broad-spectrum candidate subunit vaccine against human infection due to typhoidal and nontyphoidal Salmonella serovars.